2022
DOI: 10.3389/fimmu.2022.870183
|View full text |Cite
|
Sign up to set email alerts
|

GPR105-Targeted Therapy Promotes Gout Resolution as a Switch Between NETosis and Apoptosis of Neutrophils

Abstract: The fate of infiltrating neutrophils in inflamed joints determines the development of acute gouty arthritis (AGA). GPR105 highly expressed in human neutrophils is sensitive to monosodium urate crystals (MSU); nevertheless, the roles of GPR105 in AGA remain unclear. Here, we show that GPR105 is significantly upregulated in peripheral polymorphonuclear neutrophils of AGA patients. GPR105 knockout (GPR105−/−) prevented NETosis and induced apoptosis of neutrophils under MSU exposure, as well as attenuating inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Therefore, targeting GPR105 might be a possible therapy for acute gouty arthritis. 149 To cure multiple NET-associated diseases, further research on NETosis is needed.…”
Section: Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, targeting GPR105 might be a possible therapy for acute gouty arthritis. 149 To cure multiple NET-associated diseases, further research on NETosis is needed.…”
Section: Other Diseasesmentioning
confidence: 99%
“…Moreover, a recent study indicated that a decrease in GPR105, which is highly expressed in neutrophils and sensitive to MSU, can prevent NETosis and induce apoptosis. Therefore, targeting GPR105 might be a possible therapy for acute gouty arthritis 149 …”
Section: The Diseases Associated With Netosismentioning
confidence: 99%
“…The resulting mixture was bubbled with H 2 at rt for 5 h. The Pd/C was filtered. (12). A solution of 11 (0.012 mmol, crude reaction residue without HPLC purification) in TFA (2 mL) was refluxed in a 90 °C oil bath for 2 h. Volatiles were evaporated, and the residue was purified by RP-HPLC (C18, A: ACN, B: 10 mM TEAA, 45% → 60% A in 40 min, flow rate = 5 mL/min, t R = 21 min) to give 12 as a white powder (1.9 mg, 33% overall yield from 31): (14).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…NETosis is a major consequence of neutrophil activation by urate crystals (5), and it is increased in peripheral blood neutrophils of gout patients (47). NETosis increases tissue urate levels in a DNase‐suppressed manner, potentially mediated by extracellular neutrophil DNA accumulation (4), which colocalizes with lubricin‐degrading proteases (e.g., neutrophil elastase, CTSG released from granules) and LTF. Since NETosis is linked to formation of tophus‐like urate crystal aggregation in experimental gout (47,48), our findings could be mechanistically pertinent to gout.…”
Section: Discussionmentioning
confidence: 99%
“…Urate crystal ingestion by monocytes and macrophages stimulates NLRP3 inflammasome activation and release of interleukin‐1β (IL‐1β) (1,3). The consequent endothelial and phagocyte activation amplifies inflammatory arthritis (1,3) and promotes NETosis, which can augment tissue urate levels (4) and modulate urate crystal aggregation, tophus development, and chronicity of gouty arthritis (5).…”
Section: Introductionmentioning
confidence: 99%